Herbarium genomics retraces the origins of C4-specific carbonic anhydrase in Andropogoneae (Poaceae). Issue 3 (2nd October 2018) - Besnard, Guillaume; Bianconi, Matheus E.; Hackel, Jan; Manzi, Sophie; Vorontsova, Maria S.; Christin, Pascal-Antoine
ABSTRACT: Natural history collections are traditionally used for taxonomic research, but their relevance can extend into studies of molecular evolution as illustrated here using the example of C4 photosynthesis. This complex trait boosts growth in open and warm conditions and evolved numerous times, providing multiple comparisons among C3 and C4 relatives. Previous genomic studies relied on comparisons of model species which are often separated by long-time divergence. The large C4 group Andropogoneae (Poaceae) was usually compared to relatively distant C3 taxa. Early-diverging C4 Andropogoneae and closely related C3 taxa are known but are difficult to collect and hence have not been sequenced yet. We show here that genome scans generated from herbarium samples can be used to retrace the evolution of βca genes, which encode beta carbonic anhydrase, an enzyme of the C4 pathway. Genomic fragments encompassing βca genes were assembled for specimens of phylogenetic importance, and their comparison to model grasses made it possible to distinguish changes that happened during the transition to C4 from those that preceded or followed it. Tandem gene duplications occurred during the early grass diversification, and the duplicate that retained the ancestral alternative exon conferring chloroplast localization was later co-opted for C4 photosynthesis. Early transition to C4 photosynthesis apparently relied on an increase of the cytosolic alternative transcript without drastic changes in the βca gene, which occurred later during the diversification of C4 groups. These insights into the genomic rearrangements linked to the evolution of an adaptive trait highlight the potential of natural history collections for genomic analyses.